Helping students gain understanding and self-confidence in algebra.
jolie3000 wrote:If ƒ(x) = 2x + 1, and g(x) = 3 - x, find:
c) ƒ(x + 1)
jolie3000 wrote:f) 2ƒ(x)
jolie3000 wrote:Now I'm fairly sure I have figured out a-e for example for answer a my work was as follows:
g( f (a)) =2-2a
jolie3000 wrote:ok that makes more sense. However I still don't think I got the answer right, here's what i did for #f
ƒ(2(x))= 2(2(x)+ 1)
ƒ(2(x))= 2(2x+ 1)
ƒ(2(x))= 4x+ 2
jolie3000 wrote:Is there a website that gives an explanation and then examples with break downs. I seem to need to see an example from start to finish.
I don't understand how to write it, how to start it
ƒ(x) = 2x + 1, find 2f(x)
Do I? ƒ(2f(x)) = 2(2f(x)) +1